The problem of covering major risks in the face of global warming: What policy for insurers in the European bloc? - KALANGI KAZIAMA , Michel; MAKIADI MA KIKHELA , Serge; KALUME SADIKI , Boniface (Revue Internationale du Chercheur, 2025)
Abstract This article highlights the major risks in light of the challenges of global warming in the European bloc, known as the most industrialized in the world with 13,000 Seveso sites. The objective of this article is to establish the causal links between the two variables, including major risks and the global warming phenomenon, in order to justify their impact on the coverage policy of insurance companies in the European bloc. In this regard, 100 European companies divided into quotas on a sample of 15 insurance companies were the subject of our survey around 3 main themes, the results of which were relayed by a statistical model consolidated by the economic, ecological and managerial theories used. The perception of major risks in light of the results obtained in our study is changing paradigm following the global warming phenomenon, which modifies its frequency and influences laws and conventions on the prevention of major risks in the bloc.